Practical Arduino: Cool Projects for Open Source Hardware - Oxer, Jonathan (Apress, 2012)
Phenomenon is an overused and overloaded term, but somehow it seems appropriate for Arduino—an endeavor that has caught the attention of an astonishingly wide range of people and provided opportunities for those who might otherwise have never picked up a soldering iron or written a single line of code. From dyed-in-the-wool hardware hackers to web page developers, robotics enthusiasts to installation artists, textile students to musicians: all can be found in the Arduino community. The versatility of the platform encompassing both hardware and software, combined with its inherent openness, has captured the imagination of tens of thousands of developers. One of Arduino's many strengths is the sheer volume of information available in both printed form and on the web. Getting started is really pretty easy, as the core Arduino team intended. There are plenty of excellent introductory works already available both online and in print, so we didn't want to waste your time by providing yet another "blinking LED" tutorial. We figure that if you've gotten as far as picking up a 400+ page book about Arduino it's a good sign that you're ready for something a bit more substantial and wanting to learn more about the why rather than just the how. We don't want you to be just a color-by-numbers painter, only able to assemble other peoples’ designs by dutifully plugging in wires according to a position overlay without really understanding the meaning behind it. We want you to become a true artist, able to conceptualize, design, and assemble your own creations.